196 A Structured Literature Review of Diagnostic Processes and Pathways for People Living with Younger Onset Dementia. (16th September 2019) - Kilty, Caroline; Cahill, Suzanne; Cahill, Siobhan; Foley, Tony; Rock, Bernadette; Sweeney, Brian; McGowan, Rachel; Fox, Siobhán
Abstract: Background: Currently, 1 in 10 people diagnosed with dementia in Ireland are aged under 65, this is termed "Younger Onset Dementia" (YOD). Though small in numbers these figures (4000 people) are increasing, and important differences exist between people diagnosed with (PwYOD) and those diagnosed with later onset dementia (LOD). As dementia is normally associated with advancing age, clinicians are not always on the alert for its diagnosis in younger people. Diagnosing YOD can be especially challenging since presentation may be atypical and there is a lack of clinical ownership in this area. Methods: A structured literature review was conducted to identify optimum models of diagnostic processes and pathways for PwYOD. Two research questions were addressed: (i) what models for the diagnosis of PwYOD exist nationally and internationally, and what evidence supports these and (ii) what are the differences between diagnostic processes and pathways for PwYOD compared with PwLOD. A systematic search strategy was devised to identify all relevant scientific papers. Key databases were used, supplemented by grey literature searches. A narrative synthesis approach was undertaken to assess the literature identified. Results: Pathways and processes to the diagnosis of YOD are unclear and complex and compared with LOD, diagnosis takes more time. PwYOD are more likely to have multiple referrals to different specialists, have their memory and cognitive complaints misattributed to other factors such as depression and experience longer delays in obtaining a diagnosis. Conclusion: Few evidence-based best-practice models or guidelines for the diagnosis of YOD exist internationally. Increased awareness of the signs and symptoms of YOD among all healthcare professionals is necessary. There is a need for improved linkages to be developed between Geriatric Medicine, Neurology, Psychiatry, and Primary Care services and in certain instances for suspected cases of YOD to be referred to neurology-led memory clinics.